2020
DOI: 10.3390/cells9092120
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Benefit of the Association of Lodenafil with Mesenchymal Stem Cells on Hypoxia-induced Pulmonary Hypertension in Rats

Abstract: Pulmonary arterial hypertension (PAH) is characterized by the remodeling of pulmonary arteries, with an increased pulmonary arterial pressure and right ventricle (RV) overload. This work investigated the benefit of the association of human umbilical cord mesenchymal stem cells (hMSCs) with lodenafil, a phosphodiesterase-5 inhibitor, in an animal model of PAH. Male Wistar rats were exposed to hypoxia (10% O2) for three weeks plus a weekly i.p. injection of a vascular endothelial growth factor receptor inhibitor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 51 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…PH is marked by an increase in pulmonary vascular resistance caused by increased tone and remodeling in intrapulmonary arterioles. The SuHx model exhibits several characteristics of human PH, including histological and hemodynamic alterations [ 29 , 30 , 31 ]. Herein, it was demonstrated that SuHx rats developed PH after 21 days due to slower blood flow through the pulmonary arteries, as indicated by short PAT/PET ratio.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…PH is marked by an increase in pulmonary vascular resistance caused by increased tone and remodeling in intrapulmonary arterioles. The SuHx model exhibits several characteristics of human PH, including histological and hemodynamic alterations [ 29 , 30 , 31 ]. Herein, it was demonstrated that SuHx rats developed PH after 21 days due to slower blood flow through the pulmonary arteries, as indicated by short PAT/PET ratio.…”
Section: Discussionmentioning
confidence: 99%
“…PH was induced in rats by administration of SU5416 during exposure to hypoxia, which reproduces the severe and persistent vascular remodeling and RV failure similar to late-stage human disease [ 29 , 30 , 58 ]. This rat model, SuHx, develops more severe features than hypoxia only [ 29 , 30 , 31 ] with a progressive proliferative endotheliopathy caused by SU5416 after their return to normoxia [ 29 , 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…9,11,12 Lodenafil carbonate is a new dimeric PDE5 inhibitor structurally related to sildenafil and bearing a carbonate bridge. Although its actions on the cardiovascular system were already studied, [13][14][15] the antinociceptive activity of lodenafil carbonate has not yet been investigated, and its study in models of inflammatory and neuropathic pain is of great interest for the development of new therapeutic strategies to alleviate chronic pain.…”
Section: Introductionmentioning
confidence: 99%